Revan Index, PI Index and Revan Weighted PI Index of Möbius Function Graphs: A Comparative Study (Journal of Informatics and Mathematical Sciences, 2025)
In mathematical chemistry and graph theory, topological indices help in understanding the structure of molecular graphs. Recently, the Möbius function graph of a finite group has become a topic of interest due to its connections to algebra and topology. Despite their importance, the topological indices of Möbius function graphs have received relatively little attention. In this paper, we calculate and investigate the relationships between certain degree and distance-based topological indices, including the Revan index, the PI index, and the Revan weighted PI index, for the Möbius function graphs of finite groups.